Corruption, governance, and Nigerias uncivil society, 1999-2016 - Abada,Ifeanychukwu Michael (2019)
The interface between corruption and governance has been widely discussed, with corruption generally acknowledged as leading to poor governance outcomes. The intersection between the two is also generally believed to be a key driver of insecurity. This paper demonstrates that not only do corruption and bad governance drive conflict and insecurity, but that the latter often provide the cloaking for the perpetuation of corrupt and unaccountable governance. Using the Niger Delta militancy and the Boko Haram insurgency in South and Northeast Nigeria respectively as its units of analysis, the paper demonstrates the specific ways in which the activities of these uncivil society groupings led to the perpetration of large scale corruption and irresponsive governance in Nigeria during the period under study.